(untitled) (International Journal of Engineering and Computer Science, 2017)
This android application creates updates, deletes and retrieves records on the cloud database.Google’s android OS provides great amount of flexibility to the implementation of an android application that is as pervasive as that. The given information can be of any format like DICOM image or data file in text. The system can be evaluated using any cloud service. Users are entities like administrator and normal patient. Cloud computing makes us to use out data in pervasively, ubiquitously and in distributive manner. The app stores and retrieves the data using above principles of cloud computing. The patient health record management can be done using these capabilities of Google Android and we can also store DICOM images. This app gives prediction of risk of occurrence of a disease.